Tanya Bray letter to Thomas H. Kent regarding field notes, August 14, 1982 - Bray, Tanyaet al (1982)
Field notes contributed by Tanya Bray in a letter to Thomas H. Kent regarding incorrect dates for shorebird sighting as reported in Iowa Birdlife. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed